"Making space" in practice and education: research support services in academic libraries. Issue 8 (4th November 2014) - Anne Kennan, Mary; Corrall, Sheila; Afzal, Waseem
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – How academic libraries support the research of their parent institutions has changed as a result of forces such as changing scholarly communication practices, technological developments, reduced purchasing power and changes in academic culture. The purpose of this paper is to examine the professional and educational implications of current and emerging research support environments for academic libraries, particularly with regard to research data management and bibliometrics and discuss how do professionals and educators "make space" as new service demands arise? Design/methodology/approach – The present paper uses data from a recent survey of research support provision by academic libraries in Australia, New Zealand, the UK and Ireland, (authors 2013), and provides additional in depth analysis of the textual responses to extend the analysis in the light of forces for change in higher education. The original online questionnaire surveyed current and planned research support in academic libraries, and constraints or support needs related to service developments. It was distributed to 219 institutions in Australia, New Zealand, the UK, and Ireland, and obtained 140 valid responses (response rate of 63.9 percent). Results were analyzed using descriptive statistics with thematic categorization and coding for the textual responses. Findings – Most academic libraries surveyed are already providing or planning services in the focal areas of bibliometrics and data management. There was also increasing demand for other research support services, not the focus of the study, such as eresearch support, journal publishing platforms, and grant writing support. The authors found that while many academic libraries perceive increasing research support services as a "huge opportunity" they were constrained by gaps in staff skills, knowledge, and confidence and resourcing issues. With regard to staff education and training, it was reported they require a broader understanding of the changing research and scholarly landscape, the research cultures of different disciplines, and technological change. There was a near-universal support for development of more comprehensive, specialized, LIS education to prepare professionals for broader research support roles. Originality/value – This further analysis of the implications of our survey in relation to influences such as economics, academic culture, technology, raises questions for both educators and practitioners about the future direction of the profession and how the authors collectively "make space" as new potential services arise.